Clinical and epidemiological profile of patients with nasal manifestations of granulomatous disorders in a rural tertiary care centre - Sinha, Mohit; Hirani, Narendra; Khilnani, Ajeet Kumar; Dhamecha, Yash; Pareek, Jitendra (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: Most of the times granulomatous disorders have obvious manifestations; however, sometimes they are difficult to diagnose. A literature review reveals that patients with granulomatous diseases may be frequently incorrectly diagnosed and treated.At present limited data is available on the clinical and epidemiological profile of such patients in rural India. As such rural setup lacks the expert services of rheumatologist and the patients are frequently inconsistent with diagnostic protocols despite best efforts of the clinicians. Methods: This is a prospective study conducted in a tertiary care centre at Bhuj, Gujarat, India between January 2016 and May 2017. Patients included in the study had multi systemic complaints along with nasal manifestations such as recurrent epistaxis, saddling, synechia or swelling over nose. These patients were subjected to detailed history taking including demographic profile. They underwent detailed ENT examination, biopsies, radiological and serological tests and were discussed at multidisciplinary review meetings which involved physicians, otorhinolaryngologists, dermatologist, ophthalmologist, pathologist and radiologist. Results: Of the 19 patients included in this study, 53% patients were females. 84% (16 patients) belonged to rural household and 68% (13 patients) belonged to lower socioeconomic status. 9 patients (47%) were diagnosed with tuberculosis while Wegener’s granulomatosis and leprosy accounted for 3 cases (16%) each. 2 patients each were diagnosed with Cutaneous Leishmaniasis and fungal granulomas respectively. The average period between onset of symptoms and final diagnosis was 8 months. However, it took an average of 4.75 days after patient arrived at our centre to reach a final diagnosis. Conclusions:Early diagnosis of granulomatous disorders requires a multidisciplinary approach. The role of ENT surgeons is obvious as many granulomatous disorders have nasal manifestations. A multidisciplinary approach helps cut short the time between onset of disease and diagnosis, thus benefitting the patients by reducing the hospital stay and visits as most of these illnesses require outpatient treatment. Background: Most of the times granulomatous disorders have obvious manifestations; however, sometimes they are difficult to diagnose. A literature review reveals that patients with granulomatous diseases may be frequently incorrectly diagnosed and treated.At present limited data is available on the clinical and epidemiological profile of such patients in rural India. As such rural setup lacks the expert services of rheumatologist and the patients are frequently inconsistent with diagnostic protocols despite best efforts of the clinicians. Methods: This is a prospective study conducted in a tertiary care centre at Bhuj, Gujarat, India between January 2016 and May 2017. Patients included in the study had multi systemic complaints along with nasal manifestations such as recurrent epistaxis, saddling, synechia or swelling over nose. These patients were subjected to detailed history taking including demographic profile. They underwent detailed ENT examination, biopsies, radiological and serological tests and were discussed at multidisciplinary review meetings which involved physicians, otorhinolaryngologists, dermatologist, ophthalmologist, pathologist and radiologist. Results: Of the 19 patients included in this study, 53% patients were females. 84% (16 patients) belonged to rural household and 68% (13 patients) belonged to lower socioeconomic status. 9 patients (47%) were diagnosed with tuberculosis while Wegener’s granulomatosis and leprosy accounted for 3 cases (16%) each. 2 patients each were diagnosed with Cutaneous Leishmaniasis and fungal granulomas respectively. The average period between onset of symptoms and final diagnosis was 8 months. However, it took an average of 4.75 days after patient arrived at our centre to reach a final diagnosis. Conclusions: Early diagnosis of granulomatous disorders requires a multidisciplinary approach. The role of ENT surgeons is obvious as many granulomatous disorders have nasal manifestations. A multidisciplinary approach helps cut short the time between onset of disease and diagnosis, thus benefitting the patients by reducing the hospital stay and visits as most of these illnesses require outpatient treatment.